The Effectiveness of Blindfold Games in Teaching Vocabulary at English Education Department - Marni Bawawa (Universitas Pahlawan Tuanku Tambusai, 2022)
The study attempted to reveal the effectiveness of using the Blindfold game in affecting the students' vocabulary enrichment. The pre-experimental design with one group pre test and post test design quantitatively was used in this research. Students of the English Education Department, Musamus University, Academic Year 2020/2021 were chosed as the population, and the sample was 22 participant students of a class that had an average score in the vocabulary course. The researcher used vocabulary tests to determine students' vocabulary enrichment in pre test and post test. The results of the study show that a a significant difference between the mean scores of the pre test and post test, the mean score for the pre test was 30.909, and the post test was 69.318. Moreover, the paired sample t-test showed the sig 2 tailed value of 0.000 and less than 0.005. To sum up, the results indicate that the Blindfold game effectively affects the students' vocabulary enrichment. Keywords: effectiveness, blindfold games, vocabulary enrichment